Economic Value of Parks via Human Mental Health: An Analytical Framework - Buckley, Ralf C.; Brough, Paula (Frontiers in Ecology and Evolution, 2017)
Exposure to nature yields a wide range of mental health benefits. Improvements in mental health have substantial economic value, through: reduced mental healthcare costs; improved workplace productivity; and reduced costs of antisocial behaviour, both public and private. These economic gains represent an unquantified ecosystem service attributable to conservation. Since most individual people, and hence most politicians and policy-makers, care more about the private good of individual health than the public good of ecosystem and biodiversity conservation, calculating the economic value of nature via its contributions to human mental health could prove influential in achieving conservation goals. Here we review relevant literature, establish a framework for these calculations, and identify immediate information gaps and research priorities. Current estimates rely on assumptions, but are similar in scale to those from tourism and recreation, which do influence policy.